From Print to Stage to Screen, Across the Ocean, and to Print Again: The Odyssey of Edith Wharton’s The Old Maid - Carrillo del Saz, Juan (Journal of Audiovisual Translation, 2023)
Edith Wharton’s novella Edith Wharton’s novella The Old Maid (1922) was successively adapted into theatre (Akins, 1935) and cinema (Goulding, 1939) in the 1930s. The Spanish version of the original film adaptation (La solterona) was released in Spain in 1947; subsequently, the original novella was translated into Spanish and published early in winter that year. In this paper, I analyse the textual and contextual linkages between these translated cultural products. The translated work and the relevant censorship reports are analysed, with particular attention paid to how some excerpts had been linguistically manipulated and underwent self-censorship. The Old Maid/La solterona provides an enlightening example of how views on female empowerment are consistently manipulated via the process of dubbing. Beyond this, I offer a panoramic view of the reception of the film in Spain, focusing on how it had been (problematically) ascribed to the genre of melodrama, and how it relates to its written counterparts. This case study substantiates a transnational cultural phenomenon that had already become common in the 1940s in which the import of films plays a central role in introducing foreign literary works to Spain. Lay summary In the 1930s, Edith Wharton's short novel The Old Maid, which she had published in 1922, was turned first into a play by playwright Zoë Akins, and then into a film, by director Edmund Goulding. The Spanish version of the film, titled La solterona, was released in Spain in 1947. Shortly after, the book was translated into Spanish and published in the country. In this paper, I explore how these different versions are connected. I look at how the translation and censorship of the work changed certain parts of the story, both in the film and the book. In particular, The Old Maid (or La solterona, in Spanish) helps us understand how ideas about women's empowerment were altered when the film was dubbed (in other words, through the translation of the script). I also look at how the film was received in Spain. The critics often considered it a melodrama, although they were unwilling to use that work. I see how the translated film compares to both versions of the book (in English and Spanish). This study provides an example of how literary works were introduced to Spain through imported film, which had become a common phenomenon by the 1940s.